A Core Outcome Set to Evaluate Physical Activity Interventions for People Living With Dementia. (27th July 2019) - Gonçalves, Ana-Carolina; Samuel, Dinesh; Ramsay, Mary; Demain, Sara; Marques, Alda
Abstract: Background and Objectives: A core outcome set (COS) to evaluate physical activity (PA) interventions for people living with dementia is needed, as the development of guidelines is currently limited by important heterogeneity in this field of research. Development of COS often includes Delphi surveys, but people living with dementia are often excluded. This study aimed to reach consensus on this COS using a modified Delphi survey to enable the participation of people living with dementia. Research Design and Methods: Two stakeholders groups took part in a Delphi survey (Group 1: people living with dementia and family caregivers; Group 2: professionals from different backgrounds, including physiotherapists, occupational therapists, and researchers). Caregivers and professionals completed the survey remotely. Participants living with dementia took part face-to-face, using a card sorting strategy. The consensus process was finalized with a consensus meeting. Results: Ninety-five participants of both groups completed the modified Delphi. Of those, 11 attended the consensus meeting. The card sorting strategy was successful at including people living with dementia. Seven outcomes reached consensus: preventing falls; doing what you can do; staying healthy and fit; walking better, being able to stand up and climb stairs; feeling brighter; enjoying the moment; and, feeling useful and having a purpose. Discussion and Implications: Robust and innovative methodological strategies were used to reach a consensus on a COS (what to measure) to evaluate PA for people living with dementia. Future work will focus on the selection of the most appropriate tools to measure these outcomes (how to measure).